2015
DOI: 10.1109/ted.2015.2450760
|View full text |Cite
|
Sign up to set email alerts
|

Thermometry of Filamentary RRAM Devices

Abstract: Since thermal effects play a major role in filamentary RRAM devices, we compare the two localized thermometry methods developed for such devices. One method is based on short-pulsed measurements and the other on the measurement of minority-carrier injection from the filament into a semiconductor electrode by thermionic emission. We carried out and compared the measurements on the same functional oxide layer. Both methods indicate that the filament temperature is at least ∼550 K during device operation. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 24 publications
1
46
0
Order By: Relevance
“…[1] Several unique structures have been used to evaluate the local temperature in resistive memory devices, [196][197][198] and ultrafast transient electrical measurements were proposed to study an effective device temperature. Understanding heat and energy dissipation is crucial for the evaluation and design of devices (see also Section 4: simulation of RS), since most proposed switching mechanisms rely on thermally activated processes such as defect generation, ionic transport, etc.…”
Section: Switching Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Several unique structures have been used to evaluate the local temperature in resistive memory devices, [196][197][198] and ultrafast transient electrical measurements were proposed to study an effective device temperature. Understanding heat and energy dissipation is crucial for the evaluation and design of devices (see also Section 4: simulation of RS), since most proposed switching mechanisms rely on thermally activated processes such as defect generation, ionic transport, etc.…”
Section: Switching Mechanismmentioning
confidence: 99%
“…[1] Several unique structures have been used to evaluate the local temperature in resistive memory devices, [196][197][198] and ultrafast transient electrical measurements were proposed to study an effective device temperature. [198] Scanning thermal microscopy (SThM) [200,201] is a good candidate for measuring spatially resolved temperature with nanoscale resolution in future work. Experimental measurement of the local temperature in nanoscale devices is extremely challenging.…”
Section: Switching Mechanismmentioning
confidence: 99%
“…From the resulting electron contribution, they deduced a filament temperature of up to 1300 K . By additionally performing 3D finite elements simulations, it was shown that these results are only consistent assuming a filament diameter of 1–3 nm . Janousch et al observed an elevated filament temperature by capturing the temperature profile of a lateral µm‐sized Cr‐doped SrTiO 3 ‐based cell using infrared thermal imaging .…”
Section: Introductionmentioning
confidence: 99%
“…These differences can be critical in understanding the underlying mechanism of the imaged devices, or even changes their final functions. Thus, special care should be taken to conduct the imaging experiment, and compromise is necessary between the ideal real [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100] device and the sample for imaging.…”
Section: Resistive Switching Mechanisms In Inorganic Materialsmentioning
confidence: 99%